Rozvoj marketingového mixu prodejny BALA - Bujáková, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce se zabývá návrhem pro zlepšení úrovně současného marketingového mixu vybraného podniku. První část je věnována teoretickým poznatkům marketingu, popisuje jeho jednotlivé nástroje. Praktická část se zaměřuje na analýzu stávajícího marketingového mixu, vnitřního a vnějšího prostředí podniku. Na závěr práce jsou na základě analytické části vypracovány návrhy pro zlepšení úrovně marketingového mixu.

This diploma thesis proposes a design on improvement of the level of current marketing mix in a selected bussines. First part is devoted to marketing theoretical knowledge describing its individual tools. Second part is practical and it focuses on analysing the current marketing mix, internal and external environment of the bussines. In the conclusion, a proposal of possible improvement of the marketing mix is drawn based on the analytical part.
Development of BALA Company Retail Marketing Mix
Keywords: Marketingový mix; SWOT analýza; benchmarking; vize; hodnoty; propagace; konkurenceschopnost.; Marketing mix; SWOT analysis; benchmarking; vision; company values; promotion; competitivenes.